Supramolecular synthesis and characterization of new multicomponent forms of fluconazole - Owoyemi, Bolaji Charles Dayo (2020)
Active Pharmaceutical Ingredient (API) is the therapeutic constituent that defines the pharmacological properties and performance of the drug. Their qualities vary due to their respective physicochemical and pharmacological properties/parameters like solubility, dissolution rate, bioavailability and stability. Orally administered must present adequate parameters for an effective absorption into the systemic circulation for an optimal pharmacological response. Crystal engineering is an established route through which the problematic physicochemical and pharmacological properties of an API is optimized and re-addressed by using a new solid form, which is reached via supramolecular synthesis through synthon interactions of an API and a conformer molecule. Therefore, the selection of complementary API/coformer for the design of multicomponent structures via intermolecular interactions is achieved using tools like multicomponent screening wizard of MERCURY program and the pKa rule. This thesis presents a reproducible crystallization route for the synthesis of new pharmaceutical cocrystals and a salt of fluconazole (FLZ), an antifungal multifunctional drug. The selected coformers were the dicarboxylic acids adipic, dipicolinic, oxalic, fumaric and malic, which showed strong intermolecular interactions like O−H∙∙∙N and O−H∙∙∙O (hydrogen bond) between FLZ molecule and the dicarboxylic acid. Herein, we reported four new pharmaceutical cocrystal forms; (1:1:1) fluconazole-fumaric acid monohydrate, (1:1) fluconazole-malic acid, (1:1) fluconazole-dipicolinic acid and (1:1) fluconazole-adipic acid. In addition, a stable (1:1) fluconazolium oxalate salt was synthesized through protonation (H+) of API, i.e. a FLZ cation with an oxalate anion through N+‒H∙∙∙O− ionic bond and O–H∙∙∙O hydrogen bond. All these new structures present better solubility compared to the commercialized form. The combination of spectroscopy techniques (Raman/FTIR) and principal component analysis (PCA) was employed as tool for visualizing and screening the spectra obtained from the products of the supramolecular synthesis, therefore, facilitate the discrimination of physical mixtures of API and coformers from new desired crystal structures. The structural properties characterizations of all these reported structures was performed using X-ray diffraction (powder and single crystal), Spectroscopy (Raman and FTIR) and thermal analysis (DSC, TGA, and HSM). UV-vis spectrophotometry was employed for the determination of aqueous solubility of new crystalline structures. The results in this thesis will be present as the published papers, and annexed at the end of this thesis: Annex I – Fluconazolium oxalate: synthesis and structural characterization of a highly soluble crystalline form, CrystEngComm, 21, 1114 - 1121, 2019; Annex II – Fluconazole: Synthesis and Structural Characterization of Four New Pharmaceutical Cocrystal Forms, Crystal Growth & Design, 19, 648 - 657, 2019.